UNIVERSITY MANAGEMENT IN THE CONDITIONS OF ACADEMIC FREEDOM - S.Е. Abdugalina,; R.I. Burganova,; A.V. Mogilnaya, (Academic Journal of Physical and Chemical Sciences, 2019)
The success of the university is primarily associated with the construction of a comfortable professional environment for the creative work of its members. Therefore, the development of human capital is the basis of the university’s internal policy,” Mr. Novoseltsev emphasized. “Quite right, in fact, the policy of the university is personnel. First of all, we are talking about teachers and researchers, which is why the administrative apparatus should work, first of all, to create favorable conditions for them. Universities are becoming centers of network interactions with business and partners. Intensive interpenetration of design and administrative forms of management is taking place. The resulting noticeable changes in the role of many leading employees are perceived painfully and also require the development of new management approaches. The unifying role of such collectively accepted documents as the university’s mission and strategy is growing.